Freshwater Nematodes from Matang Wild-Life and Kubah National Park Rivers, Sarawak, Malaysia - Long, Shabdin Mohd.; Kasim, Nor Yasmin (Asian Journal of Biological and Life Sciences, 2013)
Freshwater nematode surveys were carried out at Rayu River (Matang Wildlife Centre) and Cina River (Kubah National Park) to identify the species of freshwater nematodes that inhabited both rivers and to determine the relationship between nematode density and physico-chemical parameters of the rivers water. Sampling was carried out in six stations. Eight species of nematodes namely Acanthopharynx cf. affinis, Afrodorylaimus bwana, Apodorylaimus bini, Cobbonchus palustris, Crocodorylaimus flavomaculatus, Ironus cf. ignavus, Laimydorus prolificus and Mononchulus cf. nodicaudatus were recorded in both rivers. There is no significant correlation between dissolved oxygen and temperature with nematode density. The nematodes in both rivers were possibly attracted to food provided by decomposers on dead leaves that exist in the rivers.